EXTERNAL DEBT: INDONESIA IS IN A DEBT TRAP? - Nur Feriyanto; Donny Aryanto Prabowo; Adhitya Wardhono; Ciplis Gema Qori’ah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
Countries with limited domestic funding resources, including Indonesia, urgently need external debt. External debt requires good management so that it does not become a burden or even ensnare the debtor country (debt trap). This study aims to analyze the effect of macroeconomic factors, namely budget deficit, exchange rate, foreign exchange reserves, export, and the previous year's external debt, on the accumulation of external debt. It uses time series data during the period 1990 to 2021. The data analysis method in this study used Vector Autoregressive (VAR). The Impulse Response Function results of VAR analysis showed that budget deficit and foreign exchange reserves can decrease external debt accumulation. Exchange rate depreciation also drops external debt accumulation. Meanwhile, the previous period of external debt increases the accumulation of external debt in Indonesia. This result implies that the government must be able to control the stabilization of these macroeconomic variables so that external debt can be suppressed. Then, it will not become a development burden for Indonesia. In addition, the allocation of external debt must be properly directed to productive sectors so that the interest expense can be covered by return on the use of external debt.